Utopias of one - Kotin, Joshua (Book collections on Project MUSE., 2018)
"Utopias fail. Utopias of one do not. They are perfect worlds. Yet their success comes at a cost. They are radically singular -- and thus exclusive and inimitable. Utopias of One is a major new account of utopian writing. Joshua Kotin examines how eight writers -- Henry David Thoreau, W.E.B. Du Bois, Osip and Nadezhda Mandel'shtam, Anna Akhmatova, Wallace Stevens, Ezra Pound, and J.H. Prynne -- construct utopias of one within and against modernity's two large-scale attempts to harmonize individual and collective interests: liberalism and communism. The book begins in the United States between the buildup to the Civil War and the end of Jim Crow; continues in the Soviet Union between Stalinism and the late Soviet period; and concludes in England and the United States between World War I and the end of the Cold War. The book, in this way, captures how writers from disparate geopolitical contexts resist state and normative power to construct perfect worlds -- for themselves alone. Utopias of One makes a vital contribution to debates about literature and politics, presenting innovative arguments about aesthetic difficulty, personal autonomy, and complicity and dissent. The book also models a new approach to transnational and comparative scholarship, combining original research in English and Russian to illuminate more than a century and a half of literary and political history."--